The Meaning of Natality in the Phenomenology of Political Action in H. Arendt; [el Sentido de la Natalidad en la Fenomenología de la Acción Política de H. Arendt] - Brower-Beltramin, J (Universidad Compultense Madrid, 2019)
Arendt develops a phenomenology of political action based on human experience within historical processes. In this article we review some of the central concepts of this proposal, in particular, birth, understood as guiding notion, that allows the opening of man to the world, through the action conceived by the philosopher as the pure capacity of begin all human activities. In the same way we observe the tension that is generated from this phenomenological proposal with the transcendent categorial language of philosophy, trying to transgress it, to finally return to it to account for a particular conception of the political. © 2019, Universidad Compultense Madrid. All rights reserved.